Gone to the grave : burial customs of the Arkansas Ozarks, 1850-1950 - Burnett, Abby (University Press of Mississippi Jackson, 2014)
The complicated process of preparing the dead for burial is now the province of funeral industry professionals, but this is a recent development. Until the end of World War II, especially in rural parts of the South and documented here across the Arkansas Ozarks, members of the deceased's community performed all of the jobs required for a burial. This was done to relieve the family but, in many places, taboos forbid their participation. This book documents death, burial and mourning customs in the Arkansas Ozarks for 1850 to 1950.